La gelificación de los almidones de cereales y su impacto en la calidad de pellet en el desarrollo y engorde del cerdo (Sus scrofa). - Fernández Ramírez, Kener Iván (2024)
This study analyzed the use of gelation of cereal starches and how it affects the quality of the pellet intended for feeding pigs, the texture and cohesion of the pellet are essential for feed efficiency and animal welfare, for the pig farmer, this technique offers a healthy and lower cost food that meets the nutritional needs of the pig, it is a way to use starch in the manufacture of pellets, facilitating the access of breeders to a highly usable source of protein and minerals, to describe the gelation of cereal starches and its importance in pellet quality in pigs, information was gathered from current documents research articles, virtual libraries and websites, the gelation formation process involves three-dimensional networks that retain solvents, adjusts the texture of food by retaining water in protein or polysaccharide matrices, influenced by factors such as pH, pellet efficiency to optimize growth and feed efficiency, achieves a weight gain of 0.8 kg / day and a conversion of 3.2 kg, which increased to 1.2 kg/day and improved to 2.8 kg, the gelation technique improves digestibility and nutritional quality in pig feed through the appropriate choice of solvents and functional groups, pelleting not only optimizes feed efficiency and dietary uniformity for pigs, but the composition of the raw material, including lignin and moisture, also crucially influences quality and durability during handling and transportation..